How status inequality between ethnic groups affects public goods provision: Experimental evidence on caste and tolerance for teacher absenteeism in India - Prerna Singh; Dean Spears (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This article contributes to the growing scholarship on how ethnic inequality can dampen the provision of public goods and services. On the one hand, it pushes beyond purely economic inequality to include status inequality between population groups. On other hand, it moves away from the provision of social services, conceptualized through budgetary allocations, to their effective functioning. We study one of the most serious challenges to the effective functioning of social services: the absenteeism of service providers. We provide experimental evidence that in a situation of status inequality between groups, people are more likely to be tolerant of absenteeism among service providers when the intended beneficiaries are perceived to belong to low-status ethnic groups. In particular, we present results from two complementary randomized survey experiments in India. Both show that respondents are more tolerant of teacher absenteeism when schools serve low- rather than high-caste children.
Keywords: H40; J15; O15; 330; caste; ethnic inequality; India; public goods provision; survey experiment; status; teacher absenteeism